#### Answer

a. $\quad 3h$
b. $\quad 3$

#### Work Step by Step

a.
$f(x+h)=3(x+h)-1=3x+3h-1$
$f(x+h)-f(x)=3x+3h-1-(3x-1)$
$=3x+3h-1-3x+1$
$=3h$
b.
using the result of (a),
$\displaystyle \frac{f(x+h)-f(x)}{h}=\frac{3h}{h}=\quad$ .. reduce h,
$=3$

Published by
Brooks Cole

ISBN 10:
1133607705

ISBN 13:
978-1-13360-770-0

a. $\quad 3h$
b. $\quad 3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.